How to Treat COVID-19 Patients at Home in the Italian Context: An Expert Opinion - Davide Roberto Donno; Ignazio Grattagliano; Alessandro Rossi; Pierangelo Lora Aprile; Gerardo Medea; Erik Lagolio; Guido Granata; Nicola Petrosillo; Claudio Cricelli (MDPI AG, 2021)
The impact of the coronavirus disease (COVID-19), caused by the novel coronavirus SARS-CoV-2, continues to be widespread, with more than 100 million cases diagnosed in more than 220 countries since the virus was first identified in January 2020. Although patients with mild to moderate forms of COVID-19 could be efficiently managed at home, thus reducing the pressure on the healthcare system and minimizing socio-psychological impact on patients, no trial has been proposed, conducted, or even published on COVID-19 home therapy to date. These expert opinions provide indications on the therapeutical at home management of COVID-19 patients, based on the evidence from the literature and on current guidelines.